2020
DOI: 10.14295/2238-6416.v75i2.818
|View full text |Cite
|
Sign up to set email alerts
|

Queijo Macururé fabricado em Jacaré dos Homens, AL: características físico-químicas, microbiológicas e de produção

Abstract: O queijo Macururé é produzido há cerca de 100 anos por uma única família, no povoado Caititu, localizado na cidade de Jacaré dos Homens, AL. É fabricado a partir de leite cru, por fermentação natural por meio de bactérias autóctones. Possui formato cilíndrico, textura macia, massa fechada, contendo gordura líquida no seu interior, sabor levemente ácido, lembrando manteiga de garrafa, coloração marrom, casca rígida e sem trincas, e massa cozida. Muito apreciado por seu sabor único e pela riqueza cultural e gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…It is important to note that the cheese production process influences the characteristics of the final product, especially with regard to the biochemical changes that occur during maturation, as well as the edaphoclimatic conditions of the terroir in which the cheeses are produced (McSweeney & Sousa, 2000;Silva et al, 2011). Considering the limited samples used in the present study and that there are multiple factors that can influence the lipid profile of artisanal Minas cheese, further studies are recommended to understand the fatty acid profile variation observed for cheeses from these regions.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the cheese production process influences the characteristics of the final product, especially with regard to the biochemical changes that occur during maturation, as well as the edaphoclimatic conditions of the terroir in which the cheeses are produced (McSweeney & Sousa, 2000;Silva et al, 2011). Considering the limited samples used in the present study and that there are multiple factors that can influence the lipid profile of artisanal Minas cheese, further studies are recommended to understand the fatty acid profile variation observed for cheeses from these regions.…”
Section: Resultsmentioning
confidence: 99%
“…Na análise de estafilococos coagulase positiva, todas as amostras de requeijão moreno obtiveram resultados satisfatórios (<1 UFC/g) (Tabela 1). Resultado semelhante foi encontrado por Silva et al (2020) que, ao realizar a contagem de estafilococos coagulase positiva em queijo Macururé produzido com leite cru em Jacaré dos Homens-AL, obteve valores dentro dos limites da legislação vigente para queijos de média umidade, encontrando valores <10 2 UFC/g. Sabe-se que microrganismos patogênicos não esporulados como Salmonella sp., S. aureus e E. coli são facilmente destruídos pelo processo de pasteurização convencional (aquecimento que utiliza temperaturas inferiores a 100°C por alguns minutos) (FELLOWS, 2006).…”
Section: Resultsunclassified
“…Além da grande variação observada, os valores são relativamente inferiores aos encontrados em outros estudos, como em queijos da Canastra (1,95%) (Silva et al, 2011a) e do Serro (4,39%) (Machado et al, 2004).…”
Section: Medidas E Características Físico-químicas Dos Queijosunclassified